2018
DOI: 10.1002/cche.10027
|View full text |Cite
|
Sign up to set email alerts
|

Effects of heat exposure from late sowing on the agronomic and technological quality of tetraploid wheat

Abstract: Background and objectives Heat stress is a major limiting factor to wheat yield that also impacts on grain quality, and its incidence is likely to increase. Thirty‐seven durum wheats were grown in irrigated replicated field trials over two seasons in Australia, normal sown (NS) or a 2‐month late sown (LS). Agronomic and technological quality traits were examined. Findings Later sowing exposed the crop to more days at temperatures of 30°C and above indicating more heat stress while the irrigation ensured no dro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 48 publications
4
8
0
Order By: Relevance
“…Also, large size kernels have a higher percentage of endosperm which translates to higher semolina yield. There was a strong negative correlation in this study between TGW and SCR ( r = −0.73) supported by other studies in both durum (Kadkol et al, 2020; Sissons et al, 2018) and bread wheat (Maphosa et al, 2014; Riaz, 2020) and therefore selecting for higher TGW could lower SCR. In our study, Dural, the oldest variety, showed high TGW and low SCR which goes against the trend with the year of release.…”
Section: Discussionsupporting
confidence: 86%
“…Also, large size kernels have a higher percentage of endosperm which translates to higher semolina yield. There was a strong negative correlation in this study between TGW and SCR ( r = −0.73) supported by other studies in both durum (Kadkol et al, 2020; Sissons et al, 2018) and bread wheat (Maphosa et al, 2014; Riaz, 2020) and therefore selecting for higher TGW could lower SCR. In our study, Dural, the oldest variety, showed high TGW and low SCR which goes against the trend with the year of release.…”
Section: Discussionsupporting
confidence: 86%
“…The increase in WG, DG, and GI of wheat genotypes is in agreement with Bonfil et al (2015) in common wheat and Sissons et al (2018) in durum wheat. An increase in the synthesis of gliadin-like heat shock elements (HSE), which reduces the ratio of glutenin to gliadin, and ultimately lessens the GI, may be one possible explanation ( Li et al, 2013 ).…”
Section: Discussionsupporting
confidence: 78%
“…All experiments were fertilized at the time of sowing with mono-ammonium phosphate (MAP) at the rate of 100kg ha − 1 . Weed and disease control, including irrigation, followed standard procedures described in Sissons et al (2018).…”
Section: Crusader × Rt812mentioning
confidence: 99%
“…Plant height was measured in each plot, from soil surface to tip of the awns and de ned as the average of three locations within each plot. Phenology was measured as the date of awn emergence, de ned in days from sowing to when awns on 50% of the plants in a plot were approximately 1 cm above the ag leaf auricle (Sissons et al 2018).…”
Section: Crusader × Rt812mentioning
confidence: 99%